(untitled) (Contemporary Journal of Social Science Review, 2025)
The objective of this study is to explore federal dynamics and regional disparities particularly in the context of grievances of Balochistan province. Pakistan’s history demonstrates its inability to achieve its aim of preventing separatism, particularly the 1971 establishment of Bangladesh from East Pakistan. The conflict in Balochistan, Pakistan’s biggest province has long been a major obstacle for the Pakistani federation. Balochistan’s underdevelopment, highlighting the concerning state of affairs, which the government must address immediately. Numerous uprisings against the federal government have been sparked by the deprivation experienced by Balochi’s throughout the years. As a result, different governments have occasionally used force to quell these insurgent groups. Due to their exclusion from Pakistan’s mainstream politics, the Balochis regrettably harbor a variety of grave grievances that, over time, have grown into sentiments of nationality that threaten the Pakistani federation. The methodology of this study is qualitative, while it also utilizes historical, exploratory, and descriptive approaches to identify Balochistani perspectives on Pakistan Federal authority. It suggests that the Baloch peoples’ grievances must be addressed through increased regional autonomy, financial empowerment, and increased safety measures, development of infrastructure, competent policies, training, educational initiatives, public awareness-raising, effective execution of SDGs, equal economic opportunity, political and social stability, robust governance, and global collaboration.